A comparative analysis of trade union ’s strategies to organize informal labour: a study of part time female domestic workers in Delhi. - Ms. Samiksha Kapoor (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Trade unions play an important role in society by bargaining for rights of the working class. Their importance has increased even further in the times of neoliberalism and globalization as the bargaining power of labor vis-à-vis capital has reduced in the present times. Historically, trade unions affiliated to political parties in India have focused only on male formal sector workers and ignored informal and women workers. Consequently, new trade unions came up which were apolitical in nature and claim to organize informal working women. In this paper, we do a comparative study of two such apolitical organisations which claim to organize and mobilise part time female domestic workers in Delhi. We look at their organization model, strategies and challenges in organizing paid domestic work.